2021
DOI: 10.1113/jp280637
|View full text |Cite
|
Sign up to set email alerts
|

Biological sex, not reproductive cycle, influences peripheral blood immune cell prevalence in mice

Abstract: Key points Traditionally the female sex, compared with the male sex, has been perceived as having greater variability in many physiological traits, including within the immune system. We investigated effects of biological sex and the female reproductive cycle on numbers of circulating leukocytes in C57BL/6J mice. We show that biological sex, but not female reproductive cyclicity, has a significant effect on peripheral blood immune cell prevalence and variability, and that sex differences were not consistent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 88 publications
(230 reference statements)
0
25
0
Order By: Relevance
“…This study highlights how sex-dependent differences in immune function may lead to differential outcomes in sepsis depending on various precipitating factors or other superimposed comorbidities. Interestingly, biological sex, but not female reproductive cyclicity, has been shown to influence the peripheral blood immune cell prevalence in mice ( 56 ). Specifically, it has been observed that female mice have fewer monocytes, neutrophils, and natural killer cells and that males exhibit greater variability in the peripheral blood immunophenotype ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study highlights how sex-dependent differences in immune function may lead to differential outcomes in sepsis depending on various precipitating factors or other superimposed comorbidities. Interestingly, biological sex, but not female reproductive cyclicity, has been shown to influence the peripheral blood immune cell prevalence in mice ( 56 ). Specifically, it has been observed that female mice have fewer monocytes, neutrophils, and natural killer cells and that males exhibit greater variability in the peripheral blood immunophenotype ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, biological sex, but not female reproductive cyclicity, has been shown to influence the peripheral blood immune cell prevalence in mice ( 56 ). Specifically, it has been observed that female mice have fewer monocytes, neutrophils, and natural killer cells and that males exhibit greater variability in the peripheral blood immunophenotype ( 56 ). The authors also demonstrated that the common practice of using equal numbers of male and female mice is often not appropriate and subsequently provided guidance to facilitate sample size calculations for peripheral immune cells (i.e., that consider the effects of sex) ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometry of bone marrow and peripheral blood leukocytes Blood was collected retro-orbitally in heparinized capillary tubes under isoflurane anesthesia. Peripheral blood leukocytes (monocytes, neutrophils, NK cells, CD4 1 T cells, CD8 1 T cells, and B cells) were analyzed by flow cytometry as previously described (41). Bone marrow leukocytes were flushed from femurs, disrupted with an 18-gauge needle and analyzed by flow cytometry as previously described (49).…”
Section: Ccl2-elicited Monocyte Response Assaymentioning
confidence: 99%
“…Sexual dimorphism also influences regulation of hematopoietic stem cells and innate immune signaling pathways (8,38,39), which may contribute to findings that male mice with diet-induced obesity have enhanced bone marrow myelopoiesis, as well as enhanced macrophage accumulation within adipose tissue, compared with their female counterparts (6,8). Males generally have higher levels of circulating monocytes under conditions of homeostasis (40,41) and PBMC production of TNF in response to acute inflammation is generally lower in females compared with males (40,42). Together, these data emphasize the sex-specific differences that exist in immunometabolic regulation and highlight the fact that researchers often overlook sex differences when considering mechanisms that contribute to the development and progression of obesity.…”
mentioning
confidence: 99%
See 1 more Smart Citation